A study on the importance of current asset management affecting the profit performance of Progressive Impact Corporation Berhad (PICORP) / Mohd Aizat Asmuni - Asmuni, Mohd Aizat (Faculty of Business and Management, 2009)
A substantial body of prescriptive literature has evolved dealing in whole or part with use of financial statement analysis to examine firm’s performance. Today, a number of financial statement analysis books for college, university students, academic and business purposes are available at the market that help students in their study and assist businesses to make wise decision in its financial matters. The topic of the study that will be conducted by the researcher is “A Study on The Importance of Current Asset Management Affecting the Profit Performance of Progressive Impact Corporation from the year of 2005 till 2008”. The scope of the study is about the analysis of the financial statements such as balance sheets, income statements, cash flow statements, and other financial reporting, by using ratio analysis and also comparative analysis.